Creation and initial development of the Radiology Service of the Faculty of Medicine from the Universidad Nacional de Colombia. One hundred years (2016)
The first X-rays laboratory of Hospital San Juan de Dios in Bogotá was acquired by the board of directors of the Faculty of Medicine and Natural Sciences of Universidad Nacional de Colombia, and was opened in September 1917. This laboratory was created in order to modernize the attention of patients and to promote medical education. Radiology, as a subject, was first introduced to the Medicine program curriculum of this university in 1928. It is important to note that before Gonzalo Gómez Esguerra became the first Colombian director of the laboratory, three radiologist from abroad had already taken this position.